Development of variable rate technology granular fertilizer applicator for oil palm plantations - Ishola, Tajudeen Abiodun (2013)
Currently, in the Malaysian oil palm plantation, fertilizer is applied manually or mechanically at a uniform rate without due consideration to nutrient variability. Excessive application of this fertilizer leads to contamination of ground water by increasing its mineral contents to value that is above the world health organization (WHO) limit for safe drinking water. On the other hand, a variable rate technology (VRT) fertilizer applicator promotes Green Engineering practice by encouraging reduction in excessive fertilizer application, land degradation, pollution through leaching and volatilization among others. It could also increase crop yield and profit. Unfortunately, GPS-based VRT fertilizer application could not be successfully implemented in the oil palm plantation due to tree canopy cover that hinders GPS signal reception. A novel radio frequency identification (RFID) based VRT fertilizer applicator for band application of granular fertilizer on oil palm plantation was designed, developed and evaluated. The VRT fertilizer applicator has a 1.20 ton capacity hopper, two 1.88 kg/s capacity rotary valves, two 3.33 kW @ 2850 rpm centrifugal blowers and a 5.46 kg/s @ 30 rpm screw conveyor. The VRT fertilizer applicator was mounted on a 51 kW @ 2600rpm four wheel drive (4WD), four wheel steer (4WS) universal prime mover specially designed for oil palm plantation terrain. In addition, a graphical user interface written in Visual C++ 6.0 was developed to provide a digital chart for the selection of a configuration of the VRT fertilizer applicator during field operation. Extensive laboratory calibrations were conducted on the individual sensors and machine components that make up the VRT system of the VRT fertilizer applicator. The calibrated sensors were used in the calibration of the screw conveyor, rotary valves and centrifugal blowers of the machine system. LabVIEW 2011 program was used in collecting data and saving it in real time in the computer hard disc. Factorial analysis was used to study the effects of the screw conveyor speed, rotary valve speed and the centrifugal blower speed and their interactions on the discharge rate of fertilizer. Mathematical expressions relating the fertilizer discharge rate to the screw conveyor speed, rotary valves speed, centrifugal blower speed and fertilizer bulk density and repose angle was developed using multiple linear regression analysis. The results of the test were used in programming the graphical user interface in Visual C++ 6.0. Furthermore, field tests were conducted in order to determine the response time of the VRT system, the field performance and the fertilizer distribution uniformity of the VRT fertilizer applicator. An application table which contained the geo-position of each tree; the corresponding RFID code and the amount of fertilizer to be applied on each tree was developed and stored in the database of the computer system on the VRT fertilizer applicator. The RFID reader on the VRT fertilizer applicator detected the RFID code of each tree, sent the code to the LabVIEW 2011 program which related the information to the database and triggered the control system to discharge the right amount of fertilizer to the required palm tree. An evaluation test was conducted to validate the previously developed mathematical expression for fertilizer discharge rate. The application assembly of the VRT applicator has 99.28 % and 99.09 % accuracy on the right side and left side respectively of discharging the set application rate. It took 2 to 3 seconds for the VRT applicator to respond to changes in application rate depending on the magnitude of the change. The distribution uniformity test resulted in coefficient of variation (CV) range of between 6.51 % and 10.94 % which were within the acceptable percentage range specified by ASABE standards. Furthermore, the VRT fertilizer applicator has a field capacity of 7.22 ha/h and 7.71 ha/h with field efficiencies of 0.54 and 0.52 at the travelling speed of 4.43 km/h and 4.92 km/h,respectively. At field speed of 4.92 km/h the field capacity and field efficiency of the VRT fertilizer applicator were 1.67 times and 1.49 times respectively higher than those of the (uniform rate) UR fertilizer applicator at 6 km/h. It is expected that the use of RFID technology will serve as alternative for tree crops where tree canopy has hindered proper application of GPSbased precision agriculture practices.